Citizens, democracy, and markets around the Pacific rim : congruence theory and political culture - Dalton, Russell J.; Sin, To-chʻŏl (Comparative politics (Oxford University Press), 2006)
East Asia is one of the most dynamic areas of political change in the world today-what role do citizens play in these processes of change? Drawing upon a unique set of coordinated public opinion surveys conducted by the World Values Survey, this book provides a dramatically new image of the political cultures of East Asia. - ;East Asia is one of the most dynamic areas of political change in the world today-what role do citizens play in these processes of change? Drawing upon a unique set of coordinated public opinion surveys conducted by the World Values Survey, this book provides a dramatical.